Lipoprotein-heparin-fibronectin-denatured collagen complexes enhance cholesteryl ester accumulation in macrophages (The Rockefeller University Press, 1984)
The sequestration of low-density lipoprotein (LDL) by components of the vascular extracellular matrix has long been recognized as a contributing factor to lipid accumulation during atherogenesis. The effects, however, that components of the extracellular matrix might have on LDL catabolism by scavenger cells have been little investigated. For these purposes we have prepared insoluble complexes of LDL, heparin, fibronectin, and denatured collagen (gelatin) and examined their effects on lipid accumulation, LDL uptake and degradation, and cholesteryl ester synthesis in mouse peritoneal macrophages. The results of these experiments have demonstrated that the cholesteryl ester content of macrophages incubated with a particular suspension of LDL, heparin, fibronectin, and collagen complexes is four- to fivefold that of cells incubated with LDL alone. The uptake of complexes containing 125I-LDL is rapid; however, in contrast to either endocytosed 125I-LDL or 125I-acetyl LDL, the degradation of complex-derived LDL is impaired. In addition, the uptake of complex-derived LDL stimulates the incorporation of [14C]oleic acid into cholesteryl oleate, however, the stimulation was a small fraction of that observed in cells incubated with acetyl LDL. Ultrastructurally, macrophages incubated with LDL, heparin, fibronectin, and collagen complexes did not contain many lipid droplets, but rather their cytoplasm is filled with phagosomes containing material similar in appearance to LDL-matrix complexes. These results indicate that components of the extracellular matrix can alter the catabolism of LDL by scavenger cells, suggesting that they may play a role in cellular lipid accumulation in the atherosclerotic lesion.